FAKTOR-FAKTOR YANG MEMPENGARUHI PRODUKSI DAN PENDAPATAN PETANI PADI SAWAH (Pada Gapoktan Tio Olami Desa Bongoime Kecamatan Tilongkabila Kabupaten Bone Bolango) - Suwanda, Putri Windaryati; Rauf, Asda; Boekoesoe, Yuriko (Universitas Negeri Gorontalo, 2025)
This study aims to find out: 1) the characteristict of lowlans rice farmers in the Tio Olami Combined Farmers Group (Gapoktan), Bongoime Village, Tilongkabila Subdistrict, Bone Bolango Regency, 2) the income of lowland rice farmers in the Tio Olami Combined Farmers Group (Gapoktan), Village, Tilongkabila Subdistrict, Bone Bolango Regency, and 3) the use of production factors in the production of lowland rice in the Tio Olami Combined Farmers Group (Gapoktan), Bongoime Village,Tilongkabila Subdistrict, Bone Bolango Regency. This research used several data analyses including descriptive analysis, income analysis, and multiple linier regression analysis. The results showed that the characteristics of rice farmers in the Tio OlamiCombined Farmers Group (Gapoktan),Bongoime Village,Tilongkabila Subdistrict were at the average age of 58 years, the low level of education of lowland rice farmers in the Tio OlamiCombined Farmers Group (Gapoktan),Bongoime Village, wich was still mostly elementary school graduates with a percentage of 71.6%, the average farming experience was 11 years, the average number of dependents was 3, and most of the farmers' land area wa less than 1 Ha which is cultivated with an average of 0.60 Ha, and most of the land ownership wa as Cultivators. Moreover, the average production was 20,389,619 Kg per Ha in each harvest. The average income of lowland rice farmers in the Tio Olami Combined Farmers Group (Gapoktan), Village, Tilongkabila Subdistrict, Bone Bolango Regency, every planting season was IDR 16,236,652. Production factors consisted of land area, seeds, urea fertilizer, phonska fertilizer, pesticides, and labor simultaneously had a significant effect on lowland rice production, while partially seeds, fertillizer urea and pesticide has an insignificant effect.